The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jgs.18086
|View full text |Cite
|
Sign up to set email alerts
|

The association between beta‐blockers and outcomes in patients with heart failure and concurrent Alzheimer's disease and related dementias

Abstract: Background Contemporary patients with heart failure with reduced ejection fraction (HFrEF) are older and have a higher prevalence of cognitive impairment than those studied in trials. The risk/benefit trade‐off of routine beta‐blocker (BB) use in patients with HFrEF and Alzheimer's disease and related dementias (ADRD) has not been explored. This study aimed to determine the association between BB use and outcomes among patients with HFrEF and ADRD. Methods Using a random 40% sample of Medicare Parts A, B, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Ten observational studies 10,25,37,[39][40][41][42][43][44] (n=363,784) reported similar findings in people with HFpEF 43 but increased risk in HFrEF. Discontinuation of beta-blockers in hospitalised HFrEF patients with ADHF showed 2-fold risk of mortality (RR 2.06, 95%CI 1.31-3.24, five-studies, n=178,849, I 2 =69%, very low-quality evidence, eFigure 4b) 25,39,41,42,44 and 7% increased risk of 1-year readmission compared to continuation (HR 1.07, 95%CI 1.02 to 1.13, 2-studies, n=357,782, I 2 =3%, moderate-quality evidence, Figure 2) 40,44 and no statistical difference in risk of 8-52-week hospitalisation (RR 1.00, 95% CI 0.84 to 1.19, four-studies, n=362,136, I 2 =69%, very low-quality evidence, eFigure 6b) 25,40,41,44 . ADWEs included ventricular arrythmia (n=8, 5%), AF (n=44, 3%), acute coronary artery syndrome (n=12, 8%) and syncope (n=3, 2%); but no significant change in activities of daily living (ADLs).…”
Section: (Ii) Beta-blockersmentioning
confidence: 83%
“…Ten observational studies 10,25,37,[39][40][41][42][43][44] (n=363,784) reported similar findings in people with HFpEF 43 but increased risk in HFrEF. Discontinuation of beta-blockers in hospitalised HFrEF patients with ADHF showed 2-fold risk of mortality (RR 2.06, 95%CI 1.31-3.24, five-studies, n=178,849, I 2 =69%, very low-quality evidence, eFigure 4b) 25,39,41,42,44 and 7% increased risk of 1-year readmission compared to continuation (HR 1.07, 95%CI 1.02 to 1.13, 2-studies, n=357,782, I 2 =3%, moderate-quality evidence, Figure 2) 40,44 and no statistical difference in risk of 8-52-week hospitalisation (RR 1.00, 95% CI 0.84 to 1.19, four-studies, n=362,136, I 2 =69%, very low-quality evidence, eFigure 6b) 25,40,41,44 . ADWEs included ventricular arrythmia (n=8, 5%), AF (n=44, 3%), acute coronary artery syndrome (n=12, 8%) and syncope (n=3, 2%); but no significant change in activities of daily living (ADLs).…”
Section: (Ii) Beta-blockersmentioning
confidence: 83%
“…A study of 357,030 patients hospitalised with heart failure with reduced ejection fraction (HFrEF) found that the benefit of BB in reducing mortality in HFrEF is at least maintained in patients with dementia [ 254 ]. Another prospective cohort study also did not find any association between BB use and delirium [ 255 ].…”
Section: Resultsmentioning
confidence: 99%